2008
DOI: 10.1103/physrevc.77.045201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Dirac sea on pion propagation in asymmetric nuclear matter

Abstract: We study pion propagation in asymmetric nuclear matter (ANM). One of the interesting consequences of pion propagation in ANM is the mode splitting for the different charged states of pions. First we describe the pion-nucleon dynamics using the non-chiral model where one starts with pseudoscalar (PS) πN coupling and the pseudovector (PV) representation is obtained via suitable non-linear field transformations. For both of these cases the effect of the Dirac sea is estimated. Subsequently, we present results usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Many authors have studied pion properties either restricted to the symmetric nuclear matter or performed calculations in the non-relativistic framework [24][25][26][27][28][29]. In a recent work, the authors of [30,31] have shown pionic mode splitting in asymmetric nuclear matter (ANM). Using the approximation of the hard nucleon loop and suitable density expansions, they have studied pion propagation in matter in the framework of Chiral effective Lagrangian model [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have studied pion properties either restricted to the symmetric nuclear matter or performed calculations in the non-relativistic framework [24][25][26][27][28][29]. In a recent work, the authors of [30,31] have shown pionic mode splitting in asymmetric nuclear matter (ANM). Using the approximation of the hard nucleon loop and suitable density expansions, they have studied pion propagation in matter in the framework of Chiral effective Lagrangian model [32].…”
Section: Introductionmentioning
confidence: 99%
“…Using the approximation of the hard nucleon loop and suitable density expansions, they have studied pion propagation in matter in the framework of Chiral effective Lagrangian model [32]. In [31] they presented the density and asymmetry dependent pion dispersion relations and effective masses for the various charged states of pion considering both pseudoscalar and pseudovector representation of pion-nucleon interactions. It was shown that the effective pion masses had large values in the pseudoscalar representation compared to pseudovector representation.…”
Section: Introductionmentioning
confidence: 99%
“…To get the energy variation, the real and imaginary potentials have to be evaluated at a particular radius known as radius of sensitivity of optical model potential. Unlike the strongly bound system where this evaluation is done at strong absorption radius that has very weak energy dependence, the radius of sensitivity found by the technique of crossing radius for loosely bound nuclei depends strongly on energy [5]. Considering this energy variation of crossing radius, a Gauss-weighted radial moment of real and imaginary potentials around the average radius of sensitivity has been plotted as a function of energy for 6 Li+ 58 ¢ 64 Ni.…”
Section: Resultsmentioning
confidence: 99%
“…Recently in Ref. [9], it was found that the masses split for the various charged states of the pion in ANM. Such mode splitting is, in fact, a generic feature of all the isovector mesons.…”
Section: Introductionmentioning
confidence: 99%